Cost-effectiveness of insulin degludec/insulin aspart versus biphasic insulin aspart in Chinese population with type 2 diabetes - Luo, Qiong; Zhou, Li; Zhou, Naitong; Hu, Ming (Frontiers in Public Health, 2022)
Objective: To evaluate the long-term cost effectiveness of insulin degludec/insulin aspart (IDegAsp) versus biphasic insulin aspart 30(BIAsp 30) for the treatment of patients with type 2 diabetes mellitus(T2DM) with inadequately controlled on basal insulin in China. Methods: The CORE (the Center for Outcomes Research) Diabetes Model, which has been published and verified, was used to simulate disease progression and calculate the total direct medical costs, life years (LYs) and quality-adjusted life years (QALYs) over 30 years, from the perspective of Chinese healthcare system. The patient demographic information and clinical data needed for the model were gathered from a phase III treat-to-target clinical trial (NCT02762578) and other Chinese cohort studies. Medical costs on treating diabetes were calculated based on clinical trial and local sources. The diabetes management and complications costs were derived from published literature. A discounting rate of 5% was applied to both health and cost outcomes. And one-way and probabilistic sensitivity analyses were carried out to test the reliability of the results. Results: Compared with BIAsp 30, treatment with IDegAsp was associated with an incremental benefit of 0.001LYs (12.439 vs. 12.438) and 0.280 QALYs (9.522 vs. 9.242) over a 30-year time horizon, and increased CNY(Chinese Yuan) 3,970 (388,999 vs. 385,029) for total costs. IDegAsp was cost-effective versus BIAsp 30 therapy with an incremental cost-effectiveness ratio of CNY 14,179 per QALY gained. Results were robust across a range of sensitivity analyses. Conclusion: Compared with BIAsp 30, IDegAsp was a cost-effective treatment option for people with T2DM with inadequate glycaemic control on basal insulin in China.